1996
DOI: 10.1007/bf00188094
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel Spirillum-like bacterium that degrades ferrioxamine-type siderophores

Abstract: A novel Gram-negative Spirillum-like bacterium (ASP-1) was isolated from lake water by enrichment culture on desferrioxamine B as sole source of carbon and energy. ASP-1 was able to degrade the siderophores desferrioxamine B and E. The property of siderophore degradation was inducible in the presence of desferrioxamine B. The ferric complexes, however, were not measurably degraded but served as an iron source. Degradation of desferrioxamines in culture was followed by measuring the residual ferrioxamines color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
(10 reference statements)
1
11
0
Order By: Relevance
“…Moreover, microcosms of Escherichia coli strains, which do not utilize ferioxamines as sources of iron (6), also do not show extended culturability upon incubation with ferrioxamine E (data not shown). It is unlikely that these effects are due to ferrioxamine E degradation as a source of utilizable carbon, as was recently reported for desferrioxamine B with a Spirillum spp.-like bacterium (15), since Salmonella strains did not grow in minimal media in which the only organic component was ferrioxamine (unpublished data). Rather, we propose that the phenomenon depends upon the fact that ferrioxamine E (an iron-saturated complex with 1:1 stoichiometry) not only supplies iron to bacteria that may have been severely iron starved for prolonged periods but also, by balancing release (e.g., by reduction) and use (in respiration, growth, etc.)…”
mentioning
confidence: 59%
“…Moreover, microcosms of Escherichia coli strains, which do not utilize ferioxamines as sources of iron (6), also do not show extended culturability upon incubation with ferrioxamine E (data not shown). It is unlikely that these effects are due to ferrioxamine E degradation as a source of utilizable carbon, as was recently reported for desferrioxamine B with a Spirillum spp.-like bacterium (15), since Salmonella strains did not grow in minimal media in which the only organic component was ferrioxamine (unpublished data). Rather, we propose that the phenomenon depends upon the fact that ferrioxamine E (an iron-saturated complex with 1:1 stoichiometry) not only supplies iron to bacteria that may have been severely iron starved for prolonged periods but also, by balancing release (e.g., by reduction) and use (in respiration, growth, etc.)…”
mentioning
confidence: 59%
“…M. loti's ability to mineralize DFB, a siderophore produced by the soil microbe Streptomyces pilosus and other soil Streptomyces spp. (10,31,32,36,37), is another such example.…”
Section: Discussionmentioning
confidence: 99%
“…Three siderophore-degrading microbes, a pseudomonad (33)(34)(35), Azospirillum irakense (36,37), and Mesorhizobium loti (4,7,17,39), catabolize siderophores concomitant with their growth. Neilands and colleagues (33)(34)(35) observed that their microbe, named Pseudomonas FC1, degraded the hydroxamate siderophores ferrichrome, ferrichrome A, and coprogen, with ferrichrome A being the most facile to degrade.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The better iron donation properties of mono-and dihydroxamates compared to trishydroxamates may correlate well with the role of plant (leaf)plasma membranebound ferric-chelate reductase (Brü ggemann et al 1993) which reduces ferric citrate and Fe-EDTA in a NADH-dependent mode. Although in general siderophores seem to be very resistant in soil, bacteria of the genus Azospirillum are able to degrade ferrioxamines when present as iron-free compounds (desferrioxmines) in pure culture (Winkelmann et al 1996(Winkelmann et al , 1999. This is surprising as accumulation of desferrioxamines in soil is unlikely.…”
Section: Siderophores In Soilmentioning
confidence: 99%